IMPLEMENTASI MEDIA FLASH CARD: STUDI EKSPERIMENTAL UNTUK KETERAMPILAN BERHITUNG SISWA - Riswana Maulidah; Rarasaning Satianingsih; Via Yustitia (Universitas PGRI Yogyakarta, 2021)
Counting skills are an important aspect in learning mathematics. Lack of varied use of media counting in learning, makes students experience boredom in the teaching and learning process. Flash card media is one of the media used to encourage creativity and improve student understanding such as math skills. This study aims to determine whether the average numeracy skills of third grade students in material operations taught by using flash card media is better than students who do not use media at SDN Kebondalem Mojosari, academic year 2019/2020. This research is a quantitative study of experimental design quasi type. Design used is the Posttest-Only Control Design. The study population was all students of SDN Kebondalem Mojosari. Samples were taken by simple random sampling technique so that the class III-A (experimental class) and III-B (control class). Data collection techniques used were tests with instruments consisting of 15 items. Data analysis techniques using the normality test, homogeneity test, balance test, and t test with SPSS 16 assisted. The results showed that the average numeracy skills of third grade students in material operations taught by using flash card media were significantly better than students who did not use media.